Agency problems in structured finance – a case study of European CLOs - Joachim Keller (National Bank of Belgium, 2008)
This paper is a case study that focuses on possible incentive problems in the management of Collateralized Loan Obligations (CLOs). CLOs are the most important type of special purpose vehicles in the leveraged loan market, and their managers appear to have a considerable impact on performance. Specifically, this article identifies the potential incentive, or agency, problems facing CLO managers, and the mechanisms that have been put in place to mitigate these problems. These mechanisms, including structural provisions, financial incentives and reputational concerns, should work fairly effectively. However, the analysis reveals some gaps which may allow managers to engage in certain adverse strategies. Specifically, the article raises concerns about the reliability of constraints on overall portfolio risk, the so-called portfolio tests, and about the effectiveness of reputation as a disciplining device. Both concerns are related to the benign market conditions until the summer of 2007 which – at least until now – prevented, any “stress-testing” of CLOs and differentiation between managers. This paper analyzes also evidence on CLO transactions in which managers buy/hold a portion of the equity tranche. Although retention of the equity tranche is only one of several incentive aligning mechanisms and not a general requirement, the analysis reveals that factors related to the agency problems can explain why in certain cases managers buy/hold a portion of the equity tranche. Specifically, first time managers and managers of a risky transaction buy/hold more frequently a portion of the equity tranche. Furthermore, buy/hold patterns change over time, which suggest that competitive effects and market trends play a role in the question whether to retain a portion of the equity tranche
Keywords: D82; G21; L89; 330; credit risk transfer; moral hazard; asset securitisation; CLO's; Derivat; Asset-Backed Securities; Kreditrisiko; Moral Hazard; Verbriefung; EU-Staaten